Hidracáridos (Acari, Hydrachnidia) de la cuenca Andina del río Beni, Bolivia - Rosso, Beatriz Elena (2004)
Water mites from Andean part of the Bolivian Amazonian rivers were examined. A new species is described, Limnesia aymara. New records and redescription are made for Hygrobatella multiacetabulata Cook,1980, Atractides brasiliensis (Lundblad, 1937) and Krendowskia convexa (Ribaga, 1902). A new subgenus Schwoerbelobatella for hygrobatelids poliacetabulated is proposed and characterized. Ecological characteristics of the river area sampled and ecological preferences of the analyzed species are discussed. New records and redescription are made for Hygrobatella multiacetabulata Cook,1980, Atractides brasiliensis (Lundblad, 1937) and Krendowskia convexa (Ribaga, 1902). A new subgenus Schwoerbelobatella for hygrobatelids poliacetabulated is proposed and characterized. Ecological characteristics of the river area sampled and ecological preferences of the analyzed species are discussed. New records and redescription are made for Hygrobatella multiacetabulata Cook,1980, Atractides brasiliensis (Lundblad, 1937) and Krendowskia convexa (Ribaga, 1902). A new subgenus Schwoerbelobatella for hygrobatelids poliacetabulated is proposed and characterized. Ecological characteristics of the river area sampled and ecological preferences of the analyzed species are discussed. New records and redescription are made for Hygrobatella multiacetabulata Cook,1980, Atractides brasiliensis (Lundblad, 1937) and Krendowskia convexa (Ribaga, 1902). A new subgenus Schwoerbelobatella for hygrobatelids poliacetabulated is proposed and characterized. Ecological characteristics of the river area sampled and ecological preferences of the analyzed species are discussed. New records and redescription are made for Hygrobatella multiacetabulata Cook,1980, Atractides brasiliensis (Lundblad, 1937) and Krendowskia convexa (Ribaga, 1902). A new subgenus Schwoerbelobatella for hygrobatelids poliacetabulated is proposed and characterized. Ecological characteristics of the river area sampled and ecological preferences of the analyzed species are discussed. Limnesia aymara. New records and redescription are made for Hygrobatella multiacetabulata Cook,1980, Atractides brasiliensis (Lundblad, 1937) and Krendowskia convexa (Ribaga, 1902). A new subgenus Schwoerbelobatella for hygrobatelids poliacetabulated is proposed and characterized. Ecological characteristics of the river area sampled and ecological preferences of the analyzed species are discussed.Hygrobatella multiacetabulata Cook,1980, Atractides brasiliensis (Lundblad, 1937) and Krendowskia convexa (Ribaga, 1902). A new subgenus Schwoerbelobatella for hygrobatelids poliacetabulated is proposed and characterized. Ecological characteristics of the river area sampled and ecological preferences of the analyzed species are discussed.